Competence of Visionary Leaders of Educational Institutions in the Challenges of Technology-Disruption - Emylia Handayani (Universitas Muhammadiyah Enrekang, 2023)
The visionary leadership of educational institutions is a leadership profile considered capable of carrying out the performance of educational institutions that are adaptive and anticipatory to changes or disruptive challenges in the future technological era. The development of technology has dramatically impacted educational institutions. So there needs to be a study of what strategies can be done by a visionary leader in doing his business in forming an innovative organization. It creates an organization by progress demands and equips its members to improve its performance. Therefore, this article provides direction for leaders to determine the right and fundamental strategies to answer this technological disruption's challenges. The study used in this article is literature that analyzes technology disruption, then presents a conceptual framework of academic leader skills of educational institutions in the challenges of technological disruption. The author proposes several strategies for leaders of educational institutions, namely changing the form of educational institutions, sharpening vision and paying attention to human resources, forming innovation teams, and evaluating teams. All is done to prepare human resources who can keep up with technological advances.